Electrical status epilepticus in sleep, a constitutive feature of Christianson syndrome?. (November 2018) - Mathieu, Marie-Laure; de Bellescize, Julitta; Till, Marianne; Flurin, Vincent; Labalme, Audrey; Chatron, Nicolas; Sanlaville, Damien; Chemaly, Nicole; des Portes, Vincent; Ostrowsky, Karine; Arzimanoglou, Alexis; Lesca, Gaëtan
Abstract: Christianson syndrome (CS) is a X-linked neurodevelopmental disorder, including severe intellectual disability (ID), progressive microcephaly, ataxia, autistic behaviour (ASD), near absent speech, and epilepsy. Electrical status epilepticus in sleep (ESES) has been reported in two patients. We describe five male patients from three unrelated families with Christianson syndrome caused by a pathogenic nucleotide variation or a copy-number variation involving SLC9A6 . ESES was present in three out of the five patients in the critical age window between 4 and 8 years. All patients presented with severe intellectual disability, autistic features, and hyperactivity. Epilepsy onset occurred within the first two years of life. Seizures were of various types. In the two boys with a 20-years follow-up, epilepsy was drug-resistant during childhood, and became less active in early adolescence. Psychomotor regression was noted in two patients presenting with ESES. It was difficult to assess to what extent ESES could have contributed to the pathophysiological process, leading to regression of the already very limited communication skills. The two published case reports and our observation suggests that ESES could be a constitutive feature of Christianson syndrome, as it has already been shown for other Mendelian epileptic disorders, such as GRIN2A and CNKSR2 -related developmental epileptic encephalopathies. Sleep EEG should be performed in patients with Christianson syndrome between 4 and 8 years of age. ESES occurring in the context of ID, ASD and severe speech delay, could be helpful to make a diagnosis of CS. Highlights: ESES is recorded in all patients who underwent sleep EEG in the typical age window. A sleep EEG should be performed in all CS patients between 4 and 8. ESES finding in a male patients with ID and autistic feature is a clue to the diagnosis of CS.